Evaluation of Antiradical Activity Grape Seeds and Olive (Olea europaea) Pits Extracts (Journal of Scientific Research, 2013)
The antiradical activity of grape seeds and olive pits extracts were investigated. The aim of this study is evaluating the radical scavenging activity of methanol extracts of olive pits and grape seeds and to recover a functional and antiradical compound from olive oil and fruit juices factories waste and also for environmental treatment. The antiradical properties of ripe and unripe olive pits (RIOP and URIOP) and grape seeds (IGS) that are respectively used in Iranian oil industries and fruit juices producers are examined. All seeds and pits extracts showed DPPH radical scavenging activity ranging from 24.51 to 97.06. For this purpose a methanolic extract was prepared from each of the RIOP, URIOP and IGS and their radical scavenging ability is determined with DPPH method. For this trial the effect of 3 different dilutions (100, 200 and 300 ?g/L) of RIOP, URIOP, IGS extracts was used, separately. It was appeared that in above 100 ppm concentrations the antiradical properties reaches to its maximum activity. Also, IGS extract shows better effects in 100 ppm concentrations in comparison with RIOP, URIOP and ascorbic acid. The study shows that grape seeds can be used as a rich source of functional and antiradical compound and anticancer drugs production. Keywords: Iranian olive pits; DPPH; Antiradical activity; Radical scavenging; Grape seeds.  © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  doi: http://dx.doi.org/10.3329/jsr.v6i1.16654 J. Sci. Res. 6 (1), 185-190 (2014)